Pattern of rheumatic heart disease in patients admitted at tertiary care centre of Nepal - Koirala, Prabha Chapagain; Sah, Ram Kishor; Sharma, Deewakar (Nepalese Heart Journal, 2018)
Background and Aims: As in other developing countries, Rheumatic Heart Disease (RHD) remains a major public health problem in Nepal. The most commonly affected people are children and adults in their productive years of age. The major contributing factors for high prevalence of Rheumatic Heart Disease in developing countries are poverty, illiteracy and limited access to healthcare services. The study was done to assess the basic pattern of Rheumatic Heart Disease among patients admitted at tertiary care center of Nepal: Shahid Gangalal National Heart Center. Methods: It is a cross sectional prospective study done among the patients admitted in Shahid Gangalal National Heart Center, Kathmandu. Results: RHD was more common among patients of age group 10-40 years, the most common age being 31-40 years (28.5%), with the male female ratio 1:1.6. Majority of the admitted patients had come from Central Development Region, and least number of patients had come from Far Western Region. About 46.5% of patients were illiterate and majority of patients were without any income source. Mitral valve was the most commonly affected valve (98.2%) and mitral regurgitation was the most common valvular lesion. Conclusion: RHD mainly affects children and young people of low socioeconomic group. In our study, mitral valve was the most commonly affected valve and mitral regurgitation was the most common valvular lesion. Mitral Stenosis was statistically significant in female patients while aortic regurgitation as well as aortic stenosis were significant in male patients. Nepalese Heart Journal 2018; 15(1): 29-33